Widespread human exposure to ledanteviruses in Uganda: A population study. - James G Shepherd; Shirin Ashraf; Jesus F Salazar-Gonzalez; Maria G Salazar; Robert G Downing; Henry Bukenya; Hanna Jerome; Joseph T Mpanga; Chris Davis; Lily Tong; Vattipally B Sreenu; Linda A Atiku; et al. (Public Library of Science (PLoS), 2024)
Le Dantec virus (LDV), assigned to the species Ledantevirus ledantec, genus Ledantevirus, family Rhabdoviridae has been associated with human disease but has gone undetected since the 1970s. We describe the detection of LDV in a human case of undifferentiated fever in Uganda by metagenomic sequencing and demonstrate a serological response using ELISA and pseudotype neutralisation. By screening 997 individuals sampled in 2016, we show frequent exposure to ledanteviruses with 76% of individuals seropositive in Western Uganda, but lower seroprevalence in other areas. Serological cross-reactivity as measured by pseudotype-based neutralisation was confined to ledanteviruses, indicating population seropositivity may represent either exposure to LDV or related ledanteviruses. We also describe the discovery of a closely related ledantevirus in blood from the synanthropic rodent Mastomys erythroleucus. Ledantevirus infection is common in Uganda but is geographically heterogenous. Further surveys of patients presenting with acute fever are required to determine the contribution of these emerging viruses to febrile illness in Uganda.